Being an Effective Tutor - Dona Harris (Association of American Medical Colleges, 2006)
Abstract Mercer University School of Medicine uses problem-based learning (PBL) throughout the preclinical curricula, and the success of this is dependent on the facilitation skills of the faculty members. To ensure that our faculty development programs improved the specific facilitations skills inherent to PBL, we decided to create a specific framework. Key to this framework was the belief that those who facilitate PBLs are tutors. Their primary role is to facilitate learning, rather than teach content. In order to determine what makes a good PBL tutor, in the spring of 2005, we asked first- and second-year medical students to respond to a questionnaire on positive and negative characteristics of tutors. These data, in addition to faculty responses to similar questions, provided the bases for preparing this guide for tutors, titled "Being an Effective Tutor." The guide and the six characteristics described within would be of use to schools integrating small-group activity into their preclinical years or faculty who are facilitating any type of group learning. The guide also can be used by students to develop appropriate professional expectations of their tutors. The document was presented at our annual faculty development retreat in October and is appreciated by faculty at all levels. The Dean asked to use this as the beginning of a faculty peer review system; therefore, it will be used to develop behaviors that can be documented during a tutorial.